Population growth, desertification and land degradation in the north-western Libya - Saad A.M; Shariff N.M (Proceedings of AICS - Social Sciences, 2013)
Over the last 30 years, Libya’s population has grown at rates of about 2-3% per year. According to the Department of Statistics and Census, the total population in the country was 3.23 million in 1984 and it increased to 5.5 million in 2006. Human activities and over-exploitation of the available resources are the main reasons influencing and accelerating the phenomenon of desertification in the north-western Libya. The main objective of this study is to assess the impact of population growth factor on desertification and land degradation in the region. The findings of this study suggested that the population growth rate is an important factor that influenced desertification and land degradation in the study area. Moreover, the rapid population growth and high population density in the region contributed clearly in the deterioration of the weakened and fragile environment through exploitative hypersensitive pressure caused by the growth. In addition, the overexploitation of the region resources by man had led to the deterioration of vegetation, groundwater depletion and soil erosion. These perpetuated the prevalence desertification and increased its severity in the region.Keywords: Population Growth, Desertification, Land Degradation, Overexploitation, North-western Libya.